Living on Healthy Rhythms to Overcome Cancer: A Public Therapeutic - Nikkhah, Akbar (Journal of Nutritional Therapeutics, 2015)
This policy article sets the stage for birth of a novel public science that establishes living on rhythms to minimize risks of different cancers in the overly busy modern life. Keeping body and mind away from irregularities before incursion in genes, proteomes, metaboloms, and cells and thus in the incognizant human societies of the new times, must be highly pursued. Healthy rhythms in working, eating, drinking, sleeping, entertaining, socializing, sciencing, modernizing, exercising, travelling, and contemplating must be created and maintained for a life style to not be threatened by cancer.